Evaluation of Yashada Bhasma (Ayurvedic Zinc) in Commercial Broilers - D. Padmaja, A. RAVI; B. Devasena; Ch.Sri Durga; J .Suresh (Indian Journal of Animal Nutrition, 2025)
The objective of the study was to evaluate Yashada bhasma (YB), a nano zinc oxide particle prepared by the Ayurvedic bhasmikarana process on growth, zinc retention and bioavailablity in commercial broiler chicken. The YB was prepared and characterized by traditional, physical, chemical methods and also by TEM, EDAX and DLS. In a growth trial, 360 commercial day old VENCOBB400 broiler chicks were divided at random into four treatment groups (T1 to T4) such that each treatment contained six replicates with 15 birds per replicate. Basal diets for pre-starter (1-14 d), starter (15-21d) and finisher (22-42d phases were formulated (ICAR, 2013) and they contained 33-34 mg/kg of Zn as against the recommended level of 80 mg/kg. The experimental diets were constituted by including ZnSo4 (T1) or YB (T2,T3,T4) such that the diets contained 80,40,60 and 80 mg/kg, Zn in T1,T2,T3 and T4, respectively for feeding birds during prestarter, starter and finisher phases. The experiment was carried out for a period of 42 days to study the growth performance, the Zn, Ca, P, Mn and Fe concentration in serum, zinc retention by total excreta collection method and relative zinc bioavailability by slope ratio technique. The particle size of YB was 11.2 nm with a zeta potential of -36.3 mv and its elemental composition (g/kg) by EDAX analysis was Zn, 905, Oxygen, 28.3, Fe, 26.2 , Ca, 29.8 and P, 10.6. The TEM and SAED images revealed its crystalline nature and its zinc content was 975 g/kg DM when estimated by AAS. It contained 996 g total ash, 4.2 g AIA and 16.6 g water soluble ash per kg. The body weight gain, feed intake and feed conversion ratio were not significantly different among treatments. The relative Zn bioavailability was 130, 124 and 119.5 % in birds fed on T2, T3 and T4, respectively whereas the assumed bio-availability of Zn from ZnSo4 in T1was 100%. The results of the study suggested that Yashada bhasma, had the characteristics of nano zinc oxide and its inclusion at 2.5, 2.33 and 2.83 g/100 kg feed during prestarter, starter and finisher phase to increase the dietary zinc content to 60 mg/kg was beneficial to promote optimum growth and reduce environmental pollution of zinc in the excreta.